The Relationship Between Organizational Support and Commitment with Employee Performance in the Telecommunications Sector - Jamal, Nurwidya; Soleman, Marwan Man (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2024)
Human Resources (HR) are a basic factor in organizational achievement. If an organization has outstanding human resources, it is likely that an organization will become more advanced and develop. Employees must have support and high work commitment. so that it can create performance both individually and within the organization. The research carried out at PT. Telkom, Ternate city amounted to 151 people. by taking the entire population using primary data obtained from questionnaires. This research uses multiple linear regression analysis processed by the SPSS 16 program, while hypothesis testing uses statistical tests. then test the data by testing validity, reliability and classical assumptions. the classical assumption test includes the normality test, multicollinearity test, and heteroscedasticity test. The statistical test results for the organizational support variable have a regression coefficient value of 0.053 which is positive and has a t-count value of 7.541 t table 1.655, and a significance value of 0.000 - 0.05. results obtained from the T test. For the organizational commitment variable, the calculated t value is 2.695 and the t value for the 5% distribution table is 1.655. So it can be concluded that t count t table (2,6951,655). The significance value is 0.008 - 0.05. The results of the F test carried out by researchers show that the calculated F value of F table is (15,650 3.06) with a significance value (sig) smaller than 0.05 (0.000 0.05). (H1) organizational support has a positive effect on employee performance in PT. Telkom Ternate City. (H2) organizational commitment has a positive effect on employee performance at PT. Telkom Ternate City. (H3) organizational support and organizational commitment have a positive effect on employee performance at PT. Telkom Ternate City.